TECHNOLOGY AUDIT AND ETHICAL CULTURE FOR FRAUD PREVENTION IN THE DIGITAL ERA - Astuti , Wati Aris; Rahayu, Siti Kurnia; Angelina, Sendi Azahra (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to empirically test the effect of information technology audits on fraud prevention efforts, as well as examine how ethical culture moderates the relationship between information technology audits and fraud prevention in companies. In this research methodology, a quantitative approach was used using primary data by distributing questionnaires via Google Form to 39 respondents who were employees at the company. Data analysis was carried out using a simple linear regression method with the help of SPSS version 2.3 software. The research results show that information technology audits have a significant influence on fraud prevention efforts. In addition, in this research, it was found that ethical culture plays an important role by strengthening the relationship between information technology audits and fraud prevention efforts. These findings emphasize the importance of integration between information technology, audit practices, and ethical culture in maintaining company security and integrity from potential fraud. This research makes an important contribution to the understanding of how these factors interact with each other in the context of corporate fraud prevention